2013
DOI: 10.1111/1750-3841.12109
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Various Solvent Fractions from Edible Brown Alga, Eisenia bicyclis and Its Active Compounds

Abstract: In this study, we aimed to elucidate the antioxidant capacity of Eisenia bicyclis and evaluated its antioxidant activity using various assay systems such as 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, 2,2-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) radical scavenging, reducing power ability, and content of total polyphenol. Among all the performed experiments, the ethyl acetate fraction of E. bicyclis exhibited higher antioxidant activities. From this finding, isolation and purificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…It is revealed that the DPPH radical scavenging activity was increased by the total phenolic content. This result is in accordance with that reported by Kwon et al (2013), who revealed the positive relationship between the DPPH radical scavenging activity and the increasing of phenolic contents.…”
Section: Dpph Radical Scavenging Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…It is revealed that the DPPH radical scavenging activity was increased by the total phenolic content. This result is in accordance with that reported by Kwon et al (2013), who revealed the positive relationship between the DPPH radical scavenging activity and the increasing of phenolic contents.…”
Section: Dpph Radical Scavenging Activitysupporting
confidence: 93%
“…The total phenolic content (TPC) of the ethanol extract and its fractions was determined by the literature methods involving Folin-Ciocalteu reagent and gallic acid standard (Kukula-Koch et al, 2013;Kwon et al, 2013). 1 mL of sample was mixed with 0.5 mL of Folin-Ciocalteu reagent and 5 mL of distilled water.…”
Section: Determination Of Total Phenolic Contentmentioning
confidence: 99%
“…18,19 The results indicated that these purified compounds had strong antioxidant effects. However, the anti-obesity effects of these E. bicyclis compounds and the underlying mechanism remain unknown.…”
Section: Discussionmentioning
confidence: 94%
“…18,19 Briefly, dried E. bicyclis powder (1.3 kg) was extracted twice with methanol at room temperature for 2 days. Following removal of MeOH under reduced pressure, the resulting solution was partitioned between chloroform and H 2 O, followed by ethyl acetate and H 2 O.…”
Section: Isolation Of Five Active Compounds and Structure Determinationmentioning
confidence: 99%
“…ROS formation can activate the Akt pathway, which is upstream of the NFκB pathway, and can therefore induce activation of NFκB [34]. Notably, many sea and terrestrial polyphenols are generally recognized as antioxidants and show cytoprotective effects in some cells by reducing ROS levels [20,[35][36][37]. These observations suggest that polyphenols can act as a double-edged sword, both as an antioxidant and a prooxidant.…”
Section: Discussionmentioning
confidence: 99%